Book Rerview: Carol Roy (2016) Documentary Film Festivals: Transformative Learning, Community Building and Solidarity (Concept: The Journal of Contemporary Community Education Practice Theory, 2016)
Drawing on research into three Canadian Documentary Film Festivals, Carol Roy presents a compelling case for such festivals as conduits for social connectedness, solidarity, activism/action and hope.  Ultimately, this book encourages us and inspires us to reflect on how our own educational practice can work in this way.